Preparing Teachers to Engage Rural Students in Computational Thinking Through Robotics, Game Design, and Culturally Responsive Teaching. (September 2018) - Leonard, Jacqueline; Mitchell, Monica; Barnes-Johnson, Joy; Unertl, Adrienne; Outka-Hill, Jill; Robinson, Roland; Hester-Croff, Carla
This article examines teacher preparation and teacher change in engineering and computer science education. We examined culturally responsive teaching self-efficacy (CRTSE), culturally responsive teaching outcome expectancy (CRTOE) beliefs, and attitudes toward computational thinking (CT) as teachers participated in one of three treatment groups: robotics only, game design only, or blended robotics/game design. Descriptive data revealed that CRTSE gain scores were higher in the robotics only and blended contexts than in the game design only context. However, CRTOE beliefs were consistent across all treatment groups. In regard to CT attitudes, teachers' gain scores were higher in the game design only and blended contexts than in the robotics only context. In addition, there were differences by treatment group related to STEM (science, technology, engineering, and mathematics) practices, while cultural artifacts were evident in each learning environment. The results of this study reveal some variability by treatment type and inform future research on equitable practices in engineering and computer science education.